응급부 진입구역과 환자분류구역의 감염관리를 위한 환자동선과 공간구성 계획에 대한 연구 - 강지은; 권순정 (의료·복지 건축, 2019)
Purpose: After Mers breakout in 2015, major hospital in Korea have been renovated the emergency department to make a separate infection control zone for high-risk patient with potential infection and to improve a triage area and an entrance area for efficient patient evaluation. However, there are no specific design standards to reinforce infection control for patients and staffs safety. Therefore, it is important to establish of initial design factors in the triage and entrance area as a guideline. Methods: 5 cases which had been recently renovated are selected to analyze patient circulation and spatial composition in a triage area and an entrance area. The partial floor plans of each case are represented as bubble diagrams to help understanding of different patient circulation flows. Based on this analysis, significant design factors which should be considered in planning stage for infection control have been extracted. Results: 13 design factors are established. Using these design factors, patient circulation diagram is generated to provide an optimized suggestion for efficient infection control. Implications: This suggestion provides basic databases to start to establish design guideline in the triage area and the entrance area to minimize infection spreading in the emergency department.
Keywords: Emergency Room; Triage; Emergency department zoning; Infectious Disease triage; Patient circulation; infection control; 응급부; 환자 분류시설; 감염환자 분류; 응급부 환자 동선